Genome-wide association studies in apple reveal loci of large effect controlling apple polyphenols. Issue 1 (7th September 2019) - McClure, Kendra A; Gong, YuiHui; Song, Jun; Vinqvist-Tymchuk, Melinda; Campbell Palmer, Leslie; Fan, Lihua; Burgher-MacLellan, Karen; Zhang, ZhaoQi; Celton, Jean-Marc; Forney, Charles F; Migicovsky, Zoë; Myles, Sean
Abstract: Apples are a nutritious food source with significant amounts of polyphenols that contribute to human health and wellbeing, primarily as dietary antioxidants. Although numerous pre- and post-harvest factors can affect the composition of polyphenols in apples, genetics is presumed to play a major role because polyphenol concentration varies dramatically among apple cultivars. Here we investigated the genetic architecture of apple polyphenols by combining high performance liquid chromatography (HPLC) data with ~100, 000 single nucleotide polymorphisms (SNPs) from two diverse apple populations. We found that polyphenols can vary in concentration by up to two orders of magnitude across cultivars, and that this dramatic variation was often predictable using genetic markers and frequently controlled by a small number of large effect genetic loci. Using GWAS, we identified candidate genes for the production of quercitrin, epicatechin, catechin, chlorogenic acid, 4- O -caffeoylquinic acid and procyanidins B1, B2, and C1. Our observation that a relatively simple genetic architecture underlies the dramatic variation of key polyphenols in apples suggests that breeders may be able to improve the nutritional value of apples through marker-assisted breeding or gene editing.